Prevalence of Prediabetes Among Adolescents and Young Adults in the United States, 2005-2016 - Andes, Linda J; Cheng, Yiling J; Rolka, Deborah B; Gregg, Edward W; Imperatore, Giuseppina (JAMA pediatrics, 2020)
Individuals with prediabetes are at increased risk of developing type 2 diabetes, chronic kidney disease, and cardiovascular disease. The incidence and prevalence of type 2 diabetes in the US adolescent population have increased in the last decade. Therefore, it is important to monitor the prevalence of prediabetes and varying levels of glucose tolerance to assess the future risk of type 2 diabetes in the youngest segment of the population. To examine the prevalence of impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and increased glycated hemoglobin A1c (HbA1c) levels in US adolescents (aged 12-18 years) and young adults (aged 19-34 years) without diabetes. This cross-sectional analyses of the 2005-2016 National Health and Nutrition Examination Survey assessed a population-based sample of adolescents and young adults who were not pregnant, did not have diabetes, and had measured fasting plasma glucose, 2-hour plasma glucose after a 75-g oral glucose tolerance test, and HbA1c levels. Analysis began in April 2017. Impaired fasting glucose was defined as fasting plasma glucose of 100 mg/dL to less than 126 mg/dL, IGT as 2-hour plasma glucose of 140 mg/dL to less than 200 mg/dL, and increased HbA1c level as HbA1c level between 5.7% and 6.4%. The prevalence of IFG, isolated IFG, IGT, isolated IGT, increased HbA1c level, isolated increased HbA1c level, and prediabetes (defined as having IFG, IGT, or increased HbA1c level) were estimated. Fasting insulin levels and cardiometabolic risk factors across glycemic abnormality phenotypes were also compared. Obesity was defined as having age- and sex-specific body mass index (calculated as weight in kilograms divided by height in meters squared) in the 95th percentile or higher in adolescents or 30 or higher in young adults. Of 5786 individuals, 2606 (45%) were adolescents and 3180 (55%) were young adults. Of adolescents, 50.6% (95% CI, 47.6%-53.6%) were boys, and 50.6% (95% CI, 48.8%-52.4%) of young adults were men. Among adolescents, the prevalence of prediabetes was 18.0% (95% CI, 16.0%-20.1%) and among young adults was 24.0% (95% CI, 22.0%-26.1%). Impaired fasting glucose constituted the largest proportion of prediabetes, with prevalence of 11.1% (95% CI, 9.5%-13.0%) in adolescents and 15.8% (95% CI, 14.0%-17.9%) in young adults. In multivariable logistic models including age, sex, race/ethnicity, and body mass index, the predictive marginal prevalence of prediabetes was significantly higher in male than in female individuals (22.5% [95% CI, 19.5%-25.4%] vs 13.4% [95% CI, 10.8%-16.5%] in adolescents and 29.1% [95% CI, 26.4%-32.1%] vs 18.8% [95% CI, 16.5%-21.3%] in young adults). Prediabetes prevalence was significantly higher in individuals with obesity than in those with normal weight (25.7% [95% CI, 20.0%-32.4%] vs 16.4% [95% CI, 14.3%-18.7%] in adolescents and 36.9% [95% CI, 32.9%-41.1%] vs 16.6% [95% CI, 14.2%-19.4%] in young adults). Compared with persons with normal glucose tolerance, adolescents and young adults with prediabetes had significantly higher non-high-density lipoprotein cholesterol levels, systolic blood pressure, central adiposity, and lower insulin sensitivity (P < .05 for all). In the United States, about 1 of 5 adolescents and 1 of 4 young adults have prediabetes. The adjusted prevalence of prediabetes is higher in male individuals and in people with obesity. Adolescents and young adults with prediabetes also present an unfavorable cardiometabolic risk profile, putting them both at increased risk of type 2 diabetes and cardiovascular diseases.